The Effect Of Training in achieving Organizational Commitment of workers in the organizations - محمد علي, عالية جواد (Journal of Economics and Administrative Sciences, 2016)
ABCTRACTCare research examining the relationship between the variables of search presidents (employee training and organizational commitment) to determine the effect of the training of employees in organizations in achieving organizational commitment of employees towards their organizations and by the fact that training is one of the most important activities adopted by the administration and by which can benefit realized for workers and for the organization .ttjsd problem Search lack of training considered as a factor of the important factors in the development of staff skills and development work in many Iraqi companies, including vegetable oils company (where to look), which in turn raises the relevance and commitment to worker his job as well as the increasing desire to stay in the organization and not to leave whatever the reasons. Was selected number of employees of the company as a sample for research and in a way simple random sample, which numbered 33 people working at different levels in the company researched as adopted Find the questionnaire as a tool head for data collection, which has been prepared on the basis of a number of measures ready as well as subjecting them to validity and reliability standards was used as the ready statistical program ((SPSS)) in introducing and analyzing research data has statistical methods produced a number of results mostly confirmed the existence of a link and the effect of morale among the personnel training and organizational commitment relationship, and it recommended that research on the increased attention to training which works on the development of skills workers and increase their expertise to work and so training is the best way in which they can influence the behavior of employees at various levels and hence their commitment to remain in their jobs for the possibility of achieving excellence for their company and their production in light of competition in the business market.